How does workplace ostracism affect employee innovation behavior: An analysis of chain mediating effect - Xing, Yimeng; Li, Yongzhou (Frontiers in Psychology, 2022)
With the deepening of innovation research, negative knowledge activities such as workplace ostracism and knowledge hiding are becoming new hot spots in the field of enterprise innovation and knowledge management.To explore the workplace ostracism impact on employee innovative behavior mechanism, research based on the social exchange theory, combined with the resources conservation theory and social network theory, build the knowledge hidden and workplace ostracism by organizational identification on employee innovative behavior chain mediation model, and discusses the task interdependence in the regulating function of the model.A total of 409 valid questionnaires were collected from employees of Chinese local enterprises, and AMOS and SPSS were used to empirically test the moderated chain mediation model.The results show that :(1) Workplace ostracism has a negative impact on innovation behavior;(2) Knowledge hiding and organizational identification not only play partial mediating roles between workplace ostracism and innovation behavior, but also play chain mediating roles together;(3) Task interdependence negatively moderated the positive effect of workplace ostracism on knowledge hiding.This paper puts forward the management enlightenment of constructing inclusive corporate organizational culture, constructing scientific human resource system and creating opportunities for employees to communicate.